Does Artificial Intelligence Have Concept? - Pei Li (Proceedings, 2020)
“Concept” is a commonly used word, but there are different opinions on what a “concept” is. There are those who study “concepts” from the field of cognitive science and those who study “concepts” from the field of philosophy. In recent years, people in the field of artificial intelligence have also begun to study “concept learning” related to “concept”. What is “concept learning” in artificial intelligence? Can artificial intelligence really have the same “concept” that humans have? Around these questions, this paper will analyze “concept learning of artificial intelligence” and “concept” respectively, so as to preliminarily answer the question “does artificial intelligence have concept”.